2020
DOI: 10.1152/ajpcell.00011.2020
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced, duration-dependent genome-wide DNA methylation changes in human endothelial cells

Abstract: DNA methylation, a critical epigenetic mechanism, plays an important role in governing gene expressions during biological processes such as aging, which is well known to be accelerated in hyperglycemia (diabetes). In the present study, we investigated the effects of glucose on whole genome DNA methylation in small [human retinal microvascular endothelial cells (HRECs)] and large [human umbilical vein endothelial cells (HUVECs)] vessel endothelial cell (EC) lines exposed to basal or high glucose-containing medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Methylation patterns of CpG sites across the HOTAIR gene were examined in HRECs using the Illumina Infinium Methy-lationEPIC BeadChip array (Illumina, Inc., San Diego, CA, USA), following the manufacturer's instructions and our previously published protocols (see Supplementary Materials). 16…”
Section: Methylation Analysis Of Cpg Sites Across Hotairmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation patterns of CpG sites across the HOTAIR gene were examined in HRECs using the Illumina Infinium Methy-lationEPIC BeadChip array (Illumina, Inc., San Diego, CA, USA), following the manufacturer's instructions and our previously published protocols (see Supplementary Materials). 16…”
Section: Methylation Analysis Of Cpg Sites Across Hotairmentioning
confidence: 99%
“…These findings suggest stable epigenetic DNA methylation across HOTAIR in HRECs during hyperglycemia. 16…”
Section: Glucose Does Not Cause Duration-dependent Cpg Methylation Almentioning
confidence: 99%
“…Recently, the effect of glucose on whole genome DNA methylation was studied in human retinal endothelial cells and HUVECs [165]. The lines were exposed to basal (5 mmol/L) or high (25 mmol/L) glucose-containing media for variable lengths of time.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Future analysis involving perturbation of these cell line-specific genes could provide further insight into the role of these genes in cell growth in vitro. Other studies have shown locus-specific DNA methylation changes associated with culture-specific conditions, such as length of time in culture, passage number [ 34 , 44 , 45 , 46 ], and altered levels of sera in media [ 47 , 48 , 49 ]. Similar to our analyses here, these studies generally showed global methylation patterns were maintained throughout long-term culture, but some significant differences were observed at specific CpG sites.…”
Section: Discussionmentioning
confidence: 99%